Doing What We Teach - Nario-Galace, Jasmin (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
“As an academic, I have no business thinking of solutions to problems. That is not our concern.” “The problem with you is you are in the academe, therefore, in an ivory tower. It is naive of you to call on us to say kinder words to each other and propose that we think of solutions instead.” The first quotation was from a professor-guest in a conference on an arms trade treaty attended by government officials and members of civil society organizations from Asia-Pacific, and the second was from a co-alumnus in a peace institute who was obviously irate when I suggested to the e-group to take the discussion on the Israeli-Palestine conflict to a higher level after a barrelful exchange of ugly words. The comments made above left me in disbelief. Sadly, this is how academe is perceived by many. It is an institution where theories are the name of the game, alienated from what is happening on the ground.